Nanofiltration and Tight Ultrafiltration Membranes for the Recovery of Polyphenols from Agro-Food By-Products - Cassano, Alfredo; Conidi, Carmela; Ruby-Figueroa, René; Castro-Muñoz, Roberto (International journal of molecular sciences, 2018)
Pressure-driven membrane-based technologies represent a valid approach to reduce the environmental pollution of several agro-food by-products. Recently, in relation to the major interest for natural compounds with biological activities, their use has been also addressed to the recovery, separation and fractionation of phenolic compounds from such by-products. In particular, tight ultrafiltration (UF) and nanolfiltration (NF) membranes have been recognized for their capability to recover phenolic compounds from several types of agro-food by-products. The separation capability of these membranes, as well as their productivity, depends on multiple factors such as membrane material, molecular weight cut-off (MWCO) and operating conditions (e.g., pressure, temperature, feed flow rate, volume reduction factor, etc.). This paper aims at providing a critical overview of the influence of these parameters on the recovery of phenolic compounds from agro-food by-products by using tight UF and NF membranes. The literature data are analyzed and discussed in relation to separation processes, molecule properties, membrane characteristics and other phenomena occurring in the process. Current extraction methodologies of phenolic compounds from raw materials are also introduced in order to drive the implementation of integrated systems for the production of actractive phenolic formulations of potential interest as food antioxidants.
Keywords: Food; Ultrafiltration; Nanotechnology; polyfenoly; ultrafiltrace; nanotechnologie; molekulární struktura; Membranes, Artificial; Polyphenols; potraviny; Molecular Structure; Food Analysis; membrány umělé; analýza potravin